MANAJEMEN PENGEMBANGAN WILAYAH BERBASIS KETAHANAN PANGAN - Wonda, Yarien; Sedyastuti, Kristina; Surjati, Endang (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2024)
The increasing population makes food availability a challenge in itself, especially in Puncak Jaya Regency, Indonesia. This study aims to analyze government policies in regional development based on food security, the potential for food security in supporting regional development, and the application of management systems in regional development management based on food security. The study was conducted using a qualitative research approach and data were collected from observations and interviews. The researcher used the Triangulation method. Qualitative data analysis techniques consist of three stages of activities that are interrelated with each other, namely, data reduction, data display. The condition of food security in Puncak Jaya is reviewed from the physical availability of relatively safe food with sufficient nutrition, economic accessibility to food reaches a volume with quality that is appropriate for all social groups of the population, good food security for consumers, has sustainability, namely the ability of the food system to minimize the impact of seasonal fluctuations, weather, and other fluctuations in providing food for the community and has effectiveness, which means that the regional food system is developing in an expanded reproduction pattern, the number of which increases according to the increasing food needs of the population.